Stability of Do-Not-Resuscitate Orders in Hospitalized Adults: A Population-Based Cohort Study*. Issue 2 (February 2021) - Mehta, Anuj B.; Walkey, Allan J.; Curran-Everett, Douglas; Matlock, Daniel; Douglas, Ivor S.
Abstract : Objectives: Prior work has shown substantial between-hospital variation in do-not-resuscitate orders, but stability of do-not-resuscitate preferences between hospitalizations and the institutional influence on do-not-resuscitate reversals are unclear. We determined the extent of do-not-resuscitate reversals between hospitalizations and the association of the readmission hospital with do-not-resuscitate reversal. Design: Retrospective cohort study. Setting: California Patient Discharge Database, 2016–2018. Patients: Nonsurgical patients admitted to an acute care hospital with an early do-not-resuscitate order (within 24 hr of admission). Interventions: None. Measurements and Main Results: We identified nonsurgical adult patients who survived an initial hospitalization with an early-do-not-resuscitate order and were readmitted within 30 days. The primary outcome was the association of do-not-resuscitate reversal with readmission to the same or different hospital from the initial hospital. Secondary outcomes included association of readmission to a low versus high do-not-resuscitate-rate hospital with do-not-resuscitate reversal. Among 49, 336 patients readmitted within 30 days following a first do-not-resuscitate hospitalization, 22, 251 (45.1%) experienced do-not-resuscitate reversal upon readmission. Patients readmitted to a different hospital versus the same hospital were at higher risk of do-not-resuscitate reversal (59.5% vs 38.5%; p < 0.001; adjusted odds ratio = 2.4; 95% CI, 2.3–2.5). Patients readmitted to low versus high do-not-resuscitate-rate hospitals were more likely to have do-not-resuscitate reversals (do-not-resuscitate-rate quartile 1 77.0% vs quartile 4 27.2%; p < 0.001; adjusted odds ratio = 11.9; 95% CI, 10.7–13.2). When readmitted to a different versus the same hospital, patients with do-not-resuscitate reversal had higher rates of mechanical ventilation (adjusted odds ratio = 1.9; 95% CI, 1.6–2.1) and hospital death (adjusted odds ratio = 1.2; 95% CI, 1.1–1.3). Conclusions: Do-not-resuscitate reversals at the time of readmission are more common than previously reported. Although changes in patient preferences may partially explain between-hospital differences, we observed a strong hospital effect contributing to high do-not-resuscitate-reversal rates with significant implications for patient outcomes and resource. Abstract : Supplemental Digital Content is available in the text.